Hypermethylation of MT1G and MT1H CpGs Promoter Sites and High Serum Levels of Cu Affect Survival Rate of Patients Affected by Hepatocellular Carcinoma. (29th May 2020) - Santis, Domenica De; Udali, Silvia; Ruzzenente, Andrea; Beschin, Greta; Pattini, Patrizia; Franceschi, Antonia; Moruzzi, Sara; Guglielmi, Alfredo; Olivieri, Oliviero; Choi, Sang-Woon; Friso, Simonetta
Abstract: Objectives: Recent evidences suggest a principal role of trace elements and metallothioneins (MTs), proteins involved in metal ions homeostasis and detoxification, in hepatocellular carcinogenesis. The study was designed to evaluate whether serum and liver tissue concentrations of the trace elements Cu, Zn and Se are implicated in survival rate of hepatocellular carcinoma (HCC) patients and if promoter DNA methylation is involved in trace elements-related proteins regulation. Methods: Cu, Zn and Se levels were determined in serum and liver tissue samples, both HCC and homologous non neoplastic tissue (N) of 27 HCC patients by Inductively Coupled Plasma Mass Spectrometry (ICP-MS). Gene expression analysis of MT1G and MT1H, was performed by Real-time qPCR in HCC and N tissue. Promoter DNA methylation of a region overlapping MT1G and MT1H promoters was assessed by bisulfite amplicon sequencing (BSAS) in HCC and N tissues of 23 patients. Kaplan-Meier survival curves were drawn using the log-rank test (Mantel-Cox test) to examine the differences in survival according to serum trace elements and to gene-specific methylation levels. Results: Kaplan-Meier analysis according to serum Cu levels showed that subjects within the highest quintile had an increased mortality rate (88.9%) compared with the other four quintiles ( P  = 0.025). Considering the 80th percentile of Cu levels (1118 μg/L), subjects with Cu concentrations above this value had a significantly decreased survival rate ( P  < 0.001). Se and Zn content were depleted in HCC tissues as compared to N tissues ( P  < 0.0001). MT1G and MT1H were strongly repressed in HCC tissues and precisely, MT1H in 24 out of 27 HCC tissues ( P  = 0.008) and MT1G in 23 out of 27 HCC tissues ( P  = 0.037). Nine out of 19 HCC tissues showing a down-regulation of MTs with three CpG sites, significantly hypermethylated in HCC tissue as compared to N tissue ( P  < 0.05). Considering the median methylation level, patients with higher methylation values showed increased mortality rate ( P  = 0.015). Conclusions: The significant repression of MT1G and MT1H in HCC tissue is related to promoter hypermethylation and support the hypothesis of MT1G and MT1H as possible tumor suppressor genes in HCC. The evidence of promoter methylation levels and survival rate association provide new insights for the role of DNA methylation in liver carcinogenesis. Funding Sources: N/A.